2005
DOI: 10.1111/j.1751-1097.2005.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in DNA Synthesis During Two‐photon Microscopy of Intrinsic Reduced Nicotinamide Adenine Dinucleotide Fluorescence

Abstract: Two-photon laser scanning microscopy (TPLSM) of endogenous reduced nicotinamide adenine dinucleotide (NAD(P)H) provides important information regarding the cellular metabolic state, When imaging the punctate mitochondria1 fluorescence originating from NAD(P)H in a rat basophilic leukemia (RBL) cell at low laser powers, no morphological changes are evident, and photobleaching is not observed when many images are taken. At higher powers, mitochondrial NAD(P)H fluorescence bleaches rapidly. To assess the limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previously we have demonstrated that the intrinsic fluorescence signal was appropriately modified by a mitochondrial uncoupler (p‐trifluoromethoxyphenylhydrazone) and inhibitor (sodium cyanide), indicating that the dominant source of intrinsic fluorescence generated during multiphoton microscopy at 740 nm was cellular NADH (20). The response to mitochondrial uncouplers and inhibitors and the punctate nature of the fluorescence distribution, evident in the micrograph shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we have demonstrated that the intrinsic fluorescence signal was appropriately modified by a mitochondrial uncoupler (p‐trifluoromethoxyphenylhydrazone) and inhibitor (sodium cyanide), indicating that the dominant source of intrinsic fluorescence generated during multiphoton microscopy at 740 nm was cellular NADH (20). The response to mitochondrial uncouplers and inhibitors and the punctate nature of the fluorescence distribution, evident in the micrograph shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…But this “live‐dead” assay offers only a coarse indication of biological damage. Previously we have measured a reduction of DNA synthesis in RBL cells imaged under the same conditions used in this current study (20). Changes in the level of DNA synthesis provide a very sensitive indicator of sublethal photodamage because this occurs at much lower photodynamic doses than that required to adversely affect membrane integrity or esterase activity or cause mitochondrial distress (25).…”
Section: Consequences For Two‐photon Metabolic Imaging Of Nad(p)hmentioning
confidence: 93%
See 2 more Smart Citations
“…This is the mechanism by which photodynamic therapy can kill cancer cells that have selectively absorbed photosensitizing chemicals (2,6,22). Recently, the use of two-photon absorption has been applied to cause focal cell damage (13,20,22,35). Endogenous cytosolic fluorophores, like NAD(P)H, can be visualized by both conventional and two-photon fluorescence imaging, providing insights into cell and tissue bioenergetics (22,24,38,40).…”
mentioning
confidence: 98%